Minocycline Prevents the Impairment of Hippocampal Long-Term Potentiation in the Septic Mouse. Issue 2 (August 2017) - Hoshino, Koji; Hayakawa, Mineji; Morimoto, Yuji
Abstract : ABSTRACT: Sepsis-associated encephalopathy is a major complication during sepsis, and an effective treatment remains unknown. Although minocycline (MINO) has neuroprotective effects and is an attractive candidate for treating sepsis-associated encephalopathy, the effect of MINO on synaptic plasticity during sepsis is still unclear. In the present study, we investigated the effects of MINO on long-term potentiation (LTP) in the hippocampus in a cecal ligation and puncture (CLP) mouse model. We divided mice into four groups; sham + vehicle, sham + MINO (60 mg/kg, i.p. for 3 consecutive days before slice preparation), CLP + vehicle, and CLP + MINO. We tested LTP in the CA1 region of the hippocampus, using slices taken 24 h after surgery. Because MINO is also anti-inflammatory, LTP was analyzed following 30 min of IL-1 receptor antagonist (IL-1ra) perfusion. The endotoxin level in the blood was increased at 24 h after CLP operations regardless of MINO administrations, and LTP in the CLP + vehicle group mice was severely impaired ( P < 0.05). High doses of MINO prevented the LTP impairment during sepsis in the CLP + MINO group. Interleukin (IL)-1ra administration ameliorated LTP impairment only in the CLP + vehicle group ( P < 0.05); it had no additional effects on LTP in the CLP + MINO group. In conclusion, we have provided the first evidence that MINO prevents impaired LTP related to sepsis-induced encephalopathy in the mouse hippocampus, and that mechanisms associated with IL-1 receptor activity may be involved.